2016
DOI: 10.1111/jch.12785
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Significance of N‐terminal Pro‐brain Natriuretic Peptide in Detecting the Residual Cardiovascular Risk in Hypertension and Other Clinical Conditions and in Predicting Future Cardiovascular Events

Abstract: It has been clinically demonstrated that hypertensive patients, even with controlled blood pressure (BP), have a higher incidence of cardiovascular events than normotensive patients.1 This has been attributed to an underlying residual cardiovascular risk (RCR) and is due to the fact that treatment of hypertension cannot completely reverse the sustained vascular damage as well as other cardiovascular morbid conditions. 1 Therefore, some researchers have investigated several biomarkers that better predict the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…This extra high residual CVD risk is best predicted by BNP and its inactive fragment NT-proBNP. ( 175 ) Even in treated hypertensive patients roughly 30% suffer from left ventricular hypertrophy (29%), diastolic (21%) or systolic (6%) ventricular dysfunction, left atrial expansion (15%), and silent myocardial ischemia (6%). In 13% of this group three or more of these abnormalities occur in combination ( 176 ).…”
Section: Residual Risk Factorsmentioning
confidence: 99%
“…This extra high residual CVD risk is best predicted by BNP and its inactive fragment NT-proBNP. ( 175 ) Even in treated hypertensive patients roughly 30% suffer from left ventricular hypertrophy (29%), diastolic (21%) or systolic (6%) ventricular dysfunction, left atrial expansion (15%), and silent myocardial ischemia (6%). In 13% of this group three or more of these abnormalities occur in combination ( 176 ).…”
Section: Residual Risk Factorsmentioning
confidence: 99%
“…26 In addition, the lowering of blood levels of NT-proBNP is also significant since high levels of NT-proBNP predict the onset of cardiovascular events. 27 In other studies, sacubitril/valsartan has been shown to improve insulin sensitivity in obese persons and could prevent the onset of diabetes mellitus in this population. 28 The prevention of degradation of NPs is beneficial in patients with hypertension and HF, since both conditions benefit from the diuretic, natriuretic, and vasodilating effects of NPs.…”
Section: Discussionmentioning
confidence: 89%
“…Its effects in lowering the central aortic and nocturnal BP are more important than its peripheral BP effects for the prevention of cardiovascular events . In addition, the lowering of blood levels of NT‐proBNP is also significant since high levels of NT‐proBNP predict the onset of cardiovascular events . In other studies, sacubitril/valsartan has been shown to improve insulin sensitivity in obese persons and could prevent the onset of diabetes mellitus in this population .…”
Section: Discussionmentioning
confidence: 99%